Strand Specificity and Perceived Effectiveness of Language Activities in the Senior High School English Instruction - Stephen O. Calixton; Chona G. Mascuñana (Philippine Social Science Journal, 2019)
This paper examined the level of strand specificity and perceived effectiveness of language activities in the Senior High School English for Academic and Professional Purposes (EAPP) instruction. Specifically, it determined if a difference exists in the level of strand specificity and perceived effectiveness of language activities and if there is a relationship between the two variables. Adhering to descriptive-comparative and correlational research designs, this study used a researcher-made questionnaire conducted to 79 Grade 11 Science Technology Engineering and Mathematics (STEM) students. The findings revealed a high level of strand specificity and perceived effectiveness of EAPP language activities, both when taken as a whole and grouped as oral or visual. Furthermore, no significant difference exists both between the level of strand specificity of oral and visual language activities and their perceived effectiveness. Finally, strand specificity and perceived effectiveness have a moderately positive significant relationship.